PELATIHAN MEWARNAI RAGAM HIAS TAMBUN BUNGAI SEBAGAI PENGENALAN IDENTITAS BUDAYA LOKAL DI RA HIDAYATUL INSAN PALANGKA RAYA - Romadoni, Muhamad; Asi, Yuliati Eka; Girindraswari, Nawung Asmoro; Hidayatullah, Muh. Andis; Permana, Kefas Satriya; Olala, Numeri Beny; Clara, Titha Widya (Universitas Borneo Tarakan, 2024)
Early childhood learning in kindergarten is a sensitive period that only occurs once in a lifetime. Sensitive period is a period of physical and psychological development as the children receive stimulus from the surrounding environment. RA Hidayatul Insan is one of the target partners that serves as an object in training the sensitivity of the children who attend the school. The problem that occurs is not far from the current globalization which is quite worrying. The world of fast-developing video games is preferred by children rather than honing their creativity in coloring pictures as a fun activity. In addition, the problem also seems to have an effect on the current generation in abandoning their regional cultural identity. The solution that can be offered in solving this problem is by the tambun bungai decorative coloring training as an effort to recognize cultural identity, especially in Central Kalimantan as a local culture. Many methods can be used to overcome this problem. However, the first method was direct observation of the children's habits accompanied by the socialization of the coloring program, the second was a demonstration or simulation of coloring the tambun bungai decorative pattern as a local identity, and the last activity was to conduct a workshop on coloring the tambun bungai decorative pattern together with the children. The activity aimed to encourage children to be creative in coloring the tambun bungai decorative pattern in recognizing local cultural identity. Thus, children can develop creativity in activating the right brain while recognizing the local cultural identity of the Central Kalimantan province.